Ethics Considerations Regarding Artificial Womb Technology for the Fetonate. Issue 5 (4th May 2023) - De Bie, Felix R.; Kim, Sarah D.; Bose, Sourav K.; Nathanson, Pamela; Partridge, Emily A.; Flake, Alan W.; Feudtner, Chris
Abstract: Since the early 1980's, with the clinical advent of in vitro fertilization resulting in so-called "test tube babies, " a wide array of ethical considerations and concerns regarding artificial womb technology (AWT) have been described. Recent breakthroughs in the development of extracorporeal neonatal life support by means of AWT have reinitiated ethical interest about this topic with a sense of urgency. Most of the recent ethical literature on the topic, however, pertains not to the more imminent scenario of a physiologically improved method of neonatal care through AWT, but instead to the remote scenario of "complete ectogenesis" that imagines human gestation occurring entirely outside of the womb. This scoping review of the ethical literature on AWT spans from more abstract concerns about complete ectogenesis to more immediate concerns about the soon-to-be-expected clinical life support of what we term the fetal neonate or fetonate. Within an organizing framework of different stages of human gestational development, from conception to the viable premature infant, we discuss both already identified and newly emerging ethical considerations and concerns regarding AWT and the care of the fetonate.